What Is “Too Cold?” Recess and Physical Education Weather Policies in Maine Elementary Schools - Jacobs, Lauren; Hansen, Anush; Nightingale, Christopher; Lehnard, Robert (Maine Policy Review, 2019)
This research investigated weather policies concerning outdoor recess and physical education in Maine elementary schools. Data were gathered through a statewide survey of Maine elementary school principals, interviews, and an analysis of existing policies and 10 years of historic weather data. Survey data revealed a significant correlation between geographic location and minimum cutoff temperature for outdoor recess. No relationship was found between minimum cutoff temperatures and poverty levels. There were substantial differences between the reported number of missed outdoor recess days and the estimated weather data numbers. The findings of this research are important for three reasons. First, it uncovered the vast differences in weather policies for outdoor recess and physical education in Maine. Second, there appears to be a gap in understanding about the actual number of missed outdoor recess days per year. Third, these findings may help administrators understand how changes to recess policies could increase outdoor time for students.
Keywords: recess; physical education; weather; outside; policy